PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM MEMBENTUK KEPRIBADIAN SISWA DI SMP NEGERI SATU ATAP KENDAWI GAYO LUES - Hajri Juliani; Cut Intan Hayati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
So the purpose of this study is to explain the role of Islamic Religious Education teachers and the supporting and inhibiting factors for Islamic Religious Education teachers in shaping students' personalities at SMP Negeri Satu Atap Kendawi Gayo Lues. So this study uses a qualitative method, with data collection techniques using observation, interviews, documentation. The data analysis technique used is qualitative descriptive analysis. Based on the research results, it was found that: The role of Islamic Religious Education teachers in shaping the personality of students at SMP Negeri Satu Atap Kendawi Gayo Lues is carried out by transferring knowledge (mutsaqqaf) carried out with teachings of religious values, morals, akhlakul karimah which are applied with a habitual approach, role models and advice, role models (qudwah) carried out by performing congregational prayers, reciting short verses in the morning and then reciting prayers before studying, mentors (murabbi) with habituation, role models and a functional approach by providing advice to students both individually and in groups, updating up-to-date knowledge (mujaddid al-ma'rifah) carried out by deepening the character of children who are now all digital, This behavior fosters a better student personality, enriched with new knowledge and moral values. Supporting and inhibiting factors for Islamic Religious Education (PAI) teachers in shaping student personality at SMP Negeri Satu Atap Kendawi Gayo Lues. Supporting factors include: parental motivation, a sense of shared destiny, love for the homeland, a desire for unity and a spirit of mutual cooperation, digital-based learning facilities, and competent education. Inhibiting factors include: an unfavorable student social environment, limited teacher time for guidance, supervision, and advice, inappropriate internet use, and students' tendency to follow existing trends.